The Influence of Primary Study Characteristics on the Performance Differential Between Socially Responsible and Conventional Investment Funds: A Meta-Analysis - Rathner, Sebastian (Journal of business ethics, 2013)
Empirical studies, which analyze the performance of socially responsible investment (SRI) funds relative to conventional funds, find contradictory results. The aim of this paper is to investigate, with the help of a meta-analysis, how selected primary study characteristics influence the probability of a significant under- or outperformance of SRI funds compared with conventional funds. 25 studies with more than 500 observations are included in the meta-analysis. The results of this paper suggest that the consideration of the survivorship bias in a study increases (decreases) the probability of a significant outperformance (underperformance) of SRI funds relative to conventional funds. The focus on United States (US) SRI funds increases (decreases) the probability of a significant outperformance (underperformance) too. The time period influences the probability of a significant under- and outperformance of SRI funds as well, but based on the results of this paper, it is not possible to draw general conclusions on this variable.